2022
DOI: 10.1155/2022/8090209
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Acute Postsurgical Pain over the Last Decade: A Bibliometric Analysis

Abstract: Objective. Minimizing acute postsurgical pain (APSP) remains a challenge, despite extensive research about it. This study comprehensively analyzed the literature on APSP to assess how the field has developed and where it may go in the future. Methods. Studies on APSP indexed in the Web of Science Core Collection and published from 2012 to 2021 were assessed for eligibility. Data from included studies were analyzed using CiteSpace, Python, and Microsoft. Results. Analysis of 5,236 publications on APSP showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The goal of epilepsy surgical treatment was to apply neurosurgical techniques to terminate seizures or to decrease the frequency and/or intensity of seizures while maximizing neurological function and focusing on improving the patient's quality of life. Some studies showed that temporal lobe surgery had a 60–80% chance of completely controlling seizures ( 4 ). Hippocampal sclerosis, antiepileptic drugs, children, and animal models were keywords with a large centrality, indicating that these words were the key nodes in the graph.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of epilepsy surgical treatment was to apply neurosurgical techniques to terminate seizures or to decrease the frequency and/or intensity of seizures while maximizing neurological function and focusing on improving the patient's quality of life. Some studies showed that temporal lobe surgery had a 60–80% chance of completely controlling seizures ( 4 ). Hippocampal sclerosis, antiepileptic drugs, children, and animal models were keywords with a large centrality, indicating that these words were the key nodes in the graph.…”
Section: Resultsmentioning
confidence: 99%
“…Impairment of synaptic plasticity plays a crucial role in the cognitive comorbidity of TLE ( 53 , 54 ). Inflammatory brain processes are extensively implicated in epileptogenesis ( 4 ). For instance, numerous studies have demonstrated that TLE patients' brains contain an active immune system ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CiteSpace, a free tool often used for bibliometric analysis, may provide more insights than traditional literature reviews (14). We aimed to use CiteSpace to provide the historical evolution of testicular torsion and build its relevant knowledge map, then analyzed the main research countries, institutions, key articles and keywords, so as to understand its development in the past 20 years and predict its future direction, and finally provided ideas for further research.…”
Section: Introductionmentioning
confidence: 99%
“…CiteSpace was a tool frequently employed for bibliometric analysis, providing more than the insights of traditional literature reviews (6). The knowledge map it constructs belongs to documentary scientometrics and is a visual representation of scientific knowledge, capable of mining, analysing and summarising the development process and structure of knowledge in the temporal and spatial dimensions.…”
Section: Introductionmentioning
confidence: 99%